THE CONCEPTION OF «FRAME OF SCIENCE» IN THE SYSTEM OF SCIENCE EPISTEMOLOGY OF V. VERNADSKIY - Мочалов, И. И.; Оноприенко, В. И. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
One of the key notions in Vernadskiy’s science epistemology – frame of science is analyzed. It includes mathematics, logic, the apparatus criticus of facts and empirical generalization. Frame of science is the most reliable part of science. The more variable, changeable hypotheses, theories, analogies, models and extrapolations are superstructured and twined around the frame of science.